Infographic. Strength training-induced adaptations associated with improved running economy: potential mechanisms and training recommendations - Rabello Lima, L. C.; Blagrove, R. (British Journal of Sports Medicine, 2020)
Running economy (RE) is an important determinant of distance running performance that expresses running efficiency as the oxygen uptake necessary to sustain a fixed submaximal running speed. Many interventions have been proposed to improve RE (ie, reduce oxygen uptake), with strength training (ST) being one of the most frequently investigated training strategies. The literature indicates that 6 to 14 weeks of ST intervention is likely to improve RE, especially when it emphasises the development of maximal and explosive strength. While the impact of ST on RE is well established, the mechanisms that explain this phenomenon are still debated in the literature. The aim of the present infographic is to present plausible mechanisms underpinning improvements in RE following ST.